Pengaruh antara Extraversion dan Agreeableness terhadap Depresi pada Mahasiswa yang Sedang Menempuh Tugas Akhir - Grace, Roro; Virlia, Stefani (Psychopreneur Journal, 2020)
Depression in students who are doing their final assignments is one aspect that must be considered by the university. Depression impacts on the complexity, awareness and behavior of a person. This change is caused by a person’s personality character in the face of feeling depressed. The personality character of the Indonesian people is closely related to the collectivist culture, so that extraversion and conformity are the two dimensions of the Big Five Inventory about the ability to relate selected. This research was conducted by taking a random sample of students who have criteria as students who are carrying out their final project (N = 121). Data were collected using an online questionnaire. The results showed that Extraversion affects depression, whereas Agreeableness does not affect depression.